PENGARUH INSTITUTIONAL OWNERSHIP, SALES GROWTH, DAN RASIO KEUANGAN LAINNYA TERHADAP NILAI PERUSAHAAN - Afifah, Fatin; Lekok, Widyawati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to show empirically the factors that influence firm value. This research wants to test whether variables such as institutional ownership, sales growth, capital structure, return on assets, debt to asset ratio, current ratio, and dividend payout ratio have an influence on firm value. The sampling method used in this research was a purposive sampling technique with total data obtained from 2020-2022, namely 124 sample companies from the consumer cylicals, consumer non-cylicals and healthcare sectors that met the research criteria. The analysis technique applied is the multiple regression method. This research shows that sales growth and return on assets influence firm value, while institutional ownership, capital structure, debt to asset ratio, current ratio, and dividend payout ratio do not influence firm value.